Bilateral thalamic stroke in patient with patent foramen ovale and hereditary thrombophilia - M Yu Brovko (Терапевтический архив, 2018)
Patent foramen ovale and hereditary thrombophilia are both known risk factors for ischemic stroke. Artery of Percheron is a rare anatomical variant in which vast areas of the midbrain and thalamus have a single source of blood supply. This case report presents a 45-years old female patient with bilateral thalamic stroke due to Percheron artery occlusion, with a combination of hereditary thrombophilia and patent foramen ovale as the risk factors. Modern approaches to the diagnosis and secondary prevention of this pathology are also discussed herein.